Estrategias de marketing digital y su impacto en el nivel de ventas en el Comercial El Éxito del cantón Babahoyo, periodo 2023. - Barragán Suarez, Karla Cecilia (2024)
Currently, various companies face market challenges due to increasing competition and the need to adapt to both traditional and digital marketing trends. Regardless of the economic sector they belong to, businesses strive to improve their market presence to boost sales. For this reason, this research aims to evaluate the impact of digital marketing strategies on the sales level of Comercial El Éxito in the Babahoyo canton during the 2023 period. A qualitative and quantitative approach was used methodologically, applying theoretical methods such as synthetic and analytical, as well as empirical methods like the analysis of internal and external factors. Techniques such as EFE and EFI analysis, surveys, and interviews with their respective tools were also employed. The results of this research indicate that the company is institutionally in a strong position, with strengths and opportunities outweighing weaknesses and threats, allowing it to develop growth strategies. However, it was determined that digital marketing efforts are limited, which affects the process of attracting new customers and expanding the market.In conclusion, it is recommended that the company optimize its resources to improve its presence in both traditional and digital advertising.